2018
DOI: 10.1108/ilt-03-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lubricant ageing on lubricants’ physical and chemical properties and tribological performance; Part I: effect of lubricant chemistry

Abstract: Purpose Ageing has been known to affect the performance of lubricants. However, there is a lot of debate as to whether ageing is beneficial or detrimental to the wear performance of lubricants. Design/methodology/approach The purpose of this research is to evaluate the effect of ageing on the viscosity, total acid number and Fourier-transform infrared spectroscopy information of a series of lubricants. The tribological performance (friction and wear) of the aged lubricants is also studied, followed by X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Besides, the addition of P additive into base oils experienced a huge increase. This can be related to the acidity of the P additive that has an aggressive impact on the steel surface, which has been shown in pure sliding tests shown in a previous research …”
Section: Resultsmentioning
confidence: 69%
“…Besides, the addition of P additive into base oils experienced a huge increase. This can be related to the acidity of the P additive that has an aggressive impact on the steel surface, which has been shown in pure sliding tests shown in a previous research …”
Section: Resultsmentioning
confidence: 69%
“…e formation of these acidic compounds will also increase the polarity of the oil [49]. Polar compounds can improve the strength of oil films and, therefore, enhance the lubrication ability of the oil [16,50], although such films can also be disrupted at elevated temperatures and high engine loads. For these reasons, DEALOs provide superior lubrication in the operational temperature range of − 60 to 200°C.…”
Section: Viscosity and Acid Numbermentioning
confidence: 99%
“…As to friction modifier, different tribofilm structures for fresh and aged oils were found depending on the degradation (De Feo et al , 2015b). Model mixtures of base oils and the antiwear additive zinc dialkyl dithiophosphate (ZDDP) were oxidatively aged and then subjected to tribotesting (Cen et al , 2018). In a follow-up study of Cen et al (2018), it was shown that water negatively affected the antioxidative effect of ZDDP accompanied by increase of corrosion and wear (Cen et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Model mixtures of base oils and the antiwear additive zinc dialkyl dithiophosphate (ZDDP) were oxidatively aged and then subjected to tribotesting (Cen et al , 2018). In a follow-up study of Cen et al (2018), it was shown that water negatively affected the antioxidative effect of ZDDP accompanied by increase of corrosion and wear (Cen et al , 2019). In a fully laboratory-based approach, the direct impact of oil condition, with focus on the residual amount of ZDDP and the appearance of its degradation products, on tribological performance was demonstrated (Dörr et al , 2019b).…”
Section: Introductionmentioning
confidence: 99%